High input voltage high frequency class E rectifiers for resonant inductive links - Aldhaher, Samer; Luk, Patrick Chi-Kwong; El Khamlichi Drissi, Khalil; Whidborne, James F. (IEEE, 2014)
The operation of traditional rectiﬁers such as half-wave and bridge rectiﬁers in wireless power transfer applications may be inefﬁcient and can reduce the amount of power that is delivered to a load. An alternative is to use Class E resonant rectiﬁers which are known to operate efﬁciently at high resonant frequencies and at large input voltages. Class E rectiﬁers have a near sinusoidal input current which leads to an improved overall system performance and increased efﬁciency, especially that of the transmitting coil driver. This paper is the ﬁrst to investigate the use of Class E resonant rectiﬁers in wireless power transfer systems based on resonant inductive coupling. A piecewise linear state-space representation is used to model the Class E rectiﬁer including the rectifying diode’s forward voltage drop, its ON resistance and the equivalent series resistance of the resonant inductor. Power quality parameters, such as power factor and total harmonic distortion, are calculated for different loading conditions. Extensive experimental results based on a 10 W prototype are presented to conﬁrm the performed analysis and the efﬁcient operation of the rectiﬁer. An impressive operating efﬁciency of 94.43 % has been achieved at a resonant frequency of 800 kHz.
Keywords: AC-DC power converters; High-frequency rectifiers; Inductive power tramsmission